Extension of technology continuance theory (TCT) with task technology fit (TTF) in the context of Internet banking user continuance intention. Issue 4 (8th September 2020) - Rahi, Samar; Khan, Mubbsher Munawar; Alghizzawi, Mahmoud
Abstract : Purpose: The advancement in Internet technology has played a significant role in revolutionizing the Internet banking services. Therefore, little is discussed about factors that motivate technology user to continue the use of Internet banking services. The current study investigates Internet banking user continuance behavior toward the use of Internet banking services with the integration of two-well known information system (IS) theories namely task technology fit (TTF) and technology continuance theory (TCT). Design/methodology/approach: The research design of this study is based on positivist paradigm and followed quantitative research approach. Data were collected from 360 Internet banking users of commercial banks across Pakistan. The research model was tested with structural equation modeling (SEM). Findings: The research model had explained 53.9% variance in Internet banking user continuance intention. Next to this, the predictive relevance of the research model was tested with Stone-Geisser's Q ² values using blindfolding procedure. Results revealed that the newly developed integrated technology continuance research model has substantial power to predict Internet banking user continuance intention. Moreover, the effect size analysis revealed that factors like satisfaction and user expectation were the most important factors in determining Internet banking user continuance intention. Practical implications: For practical implications importance performance matrix analysis (IPMA) has used to see the importance and performance of the underpinned factors. Findings indicate that managers and policy makers should focus on user satisfaction, perceived usefulness and expectation confirmation in order to enhance the Internet banking user continuance intention toward the use of Internet banking services. Some of the ways banks can do this is to develop esthetic Internet banking website with charm of novelty, relevant information and smooth flows with less complex redirects. Originality/value: Unlike prior studies that focus on Internet banking user pre-adoption issues, the current study examines post-adoption issue of Internet banking users and investigates Internet banking user continuance intention. This study is significant as it integrates two-well known theories namely TCT and TTF in Internet banking user continuance intention and augments the IS literature by developing an integrated technology continuance model (TCM).